1999
DOI: 10.1034/j.1399-0039.1999.530205.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary relationships between HLA‐B alleles as indicated by an analysis of intron sequences

Abstract: The HLA-B locus is the most polymorphic of the class I genes encoded within the human major histocompatibility complex. This polymorphism is mainly located in exons 2 and 3, which code for the molecule's alpha1 and alpha2 domains and includes the antigenic peptide binding site. However, information about adjacent non-coding regions (introns 1 and 2) has not been extensively reported but could be very important in establishing an understanding of the evolutionary mechanisms involved in the polymorphism generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Serologically distinct molecules, B71 and B72 (subtypes of B70), are also encoded by alleles in the B15 family. Although B15/70 is found at high frequencies in all ethnic groups, alleles encoding these specificities and their frequencies are apt to be different in distinct populations [5][6][7]. [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serologically distinct molecules, B71 and B72 (subtypes of B70), are also encoded by alleles in the B15 family. Although B15/70 is found at high frequencies in all ethnic groups, alleles encoding these specificities and their frequencies are apt to be different in distinct populations [5][6][7]. [8].…”
Section: Introductionmentioning
confidence: 99%
“…[8]. The corresponding sequences from HLAB*1504, 1515, 1539, 4901 were obtained from Gomez Casado et al [5,6] and HLA-B*15170102, 151702, 1566, 4504, 47010101, 5001, 5401, and 5512 allele sequences were taken from IMGT-HLA database (www.ebi.ac.uk/imgt/hla) [1]. The intron compilation by Cereb et al [9] was also used.…”
Section: Introductionmentioning
confidence: 99%
“…Alleles HLA-A*01:01 and HLA-B*07:02 are reported as part of the polymorphism of some groups of healthy Mexican mestizos with a frequency of 9-14%. In the case of HLA-A*03:01, it was documented with a frequency lower than the previous (0.024%) [32,33].…”
Section: Discussionmentioning
confidence: 91%
“…[5][6][7][8] Studies on intronic sequences revealed that intron 1 sequences present remarkably specific characteristics that help to identify the different HLA-B serological families and also confer upon them a phylogenetic support. 9 By contrast, introns 2 and 3 are characterized by a greater level of discordance among topologies. 10 In contrast to the 5 0 part of the HLA-B gene, which in this work is defined as the part that comprises exons 1-3, and introns 1-3, only limited sequence data 11,12 exist about its 3 0 part (exons 4-7, introns 4-6), the latter encoding the a3, transmembrane and cytoplasmatic domains.…”
Section: Introductionmentioning
confidence: 99%